Harnessing the potential of CAR-T cell in lupus treatment: From theory to practice - Alsuliman, Tamim; Marjanovic, Zora; Rimar, Doron; Tarte, Karin; Avcin, Tadej; Hagen, Melanie; Schett, Georg; Farge, Dominique (Autoimmunity Reviews, 2024)
Systemic Lupus Erythematosus (SLE) is a rare, heterogeneous, potentially life-threatening autoimmune disease. Presence of kidney or other major organ (brain, heart or lung) involvement are predictors of poor outcome and in a subset of patients resistant to 1st or 2nd line conventional treatment. The 10-year mortality remains around 10–15 %. Chimeric Antigen Receptors (CAR) are molecules that allow to redirect the engineered immune cells towards specific target antigens and to simultaneously boost their activation. Following breakthrough results observed in the treatment of hematological malignancies, conventional CAR T-cell therapy has recently been applied to refractory SLE patients. Compared to the use of monoclonal antibodies, anti-CD19 CAR T-cells allow to achieve deeper depletion of autoreactive B cells, notably at site of inflamed tissues and lymphoid organs (i.e. lymph node), to suppress interferon signature and to restore the immune tolerance with the reemergence of naïve B-cells with a new repertoire. All clinical data reported in SLE patients so far showed that autologous anti-CD19 CAR T-cell treatment allowed impressive short- and longer-term resolution of lupus nephritis and other severe disease-related manifestations, without major toxicities and only mild cytokine-release syndrome. These clinical effects persisted after B-cell reconstitution and were associated with normalization of double-stranded DNA antibodies and complement levels in drug-free patients until three years after the procedure. Overall, these pioneering experiences show unique clinical and immunological response to CAR T-cell therapy in SLE, and the need for extended follow-up to determine its long-term efficacy.
CRIS-Team Scopus Importer:2024-11-22
Keywords: B and T lymphocytes; Cell and gene therapies; Chimeric antigen receptors (CAR); Immune tolerance; Plasma cells; Systemic lupus erythematosus